Religious Tourism as a Tradition of the Christian Community: Religious Tourism as a Tradition of the Christian Community - Wiharjokusumo, Padriadi; Saragih, Novita Romauli (Jurnal Ilmiah Akomodasi Agung, 2023)
Religious tourism represents a compelling form of travel that captures the interest of many individuals, particularly those of the Christian faith. It involves activities undertaken by Christian believers to visit places imbued with religious significance, such as churches, monasteries, holy tombs, or historical sites associated with the Christian religion. Religious tourism offers numerous benefits to pilgrims, ranging from the enhancement of faith and the broadening of perspectives to gaining insight into local cultures or simply enjoying a leisurely vacation. Additionally, this form of tourism can have positive impacts on local communities, contributing to economic growth, the preservation of traditions, and the promotion of interfaith tolerance. The research indicates that Christian individuals engage in religious tourism not only to deepen their spiritual understanding but also to actively contribute to communal activities that advance unity and brotherhood among different groups. The study underscores the significance of religious tourism as a means of not only personal spiritual growth but also as a catalyst for fostering intergroup harmony within the Christian community. Keywords: Wisata, Religion, Tradition, Christianity.